Chronic Myeloid Leukemia and Associated Oral Manifestations (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Leukemia defined as a hematological disorder associated with proliferating white blood cellforming tissues as resultant increasing of circulating immature white blood cells or abnormal cells.Aims of the study: To investigate clinically the oral manifestations or discomfort oral features in patientswith chronic myeloid leukemia.Subjects, Materials and Methods: Thirty- three patients participated (17 males and 16 females) in thecurrent study with chronic myeloid leukemia already.Results: Total numbers of cases were (33). (17 males and 16 females), the percentages of these resultsshowed gingival bleeding (87%), fungal infection (84%), oral petechiae (72%), gingival overgrow (63%),and then finally painless oral ulceration (60%), The early diagnosis of this disease knowing that the firstclinical symptoms of leukemia happen in the oral cavity with normal or show challenging changes in initiallaboratory tests.Conclusions: Because of their clinical importance for early diagnosis, all such lesions or pathological statusdeserves the full attention of the doctors (like oral physician and general physician).